STRUKTUR KOMUNITAS SERANGGA POLINATOR DI KEBUN BUAH AGRIBISNIS FAKULTAS PERTANIAN UNIVERSITAS RIAU SEBAGAI PENGEMBANGAN LEMBAR KERJA SISWA KONSEP INTERAKSI DALAM EKOSISTEM KELAS X SMA - Khairi, Kurnia Khairi; Febrita, Elya Febrita; ', Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research was to determine community structure of pollinator insects in fruit garden Agribusiness Agriculture Faculty University of Riau in March to April 2015, for development of Student Worksheet (LKS) interactions the ecosystem concept. The research was conducted with 2 phases of field research and the development of learning worksheets. Determining the location of the observation by purposive sampling to establish the location of the observation at 5 fruit garden Agribusiness Agriculture Faculty University of Riau. Biological parameters observed that the abundance of species, dominance index and preferences visits, while the environmental physical parameters include temperature, humidity and light intensity. The results showed the highest relative abundance is Apis cerana, insect pollinators dominance index was low (0,189 to 0,363) and the highest preference insect pollinators in the afternoon (15:00 to 17:00). Results of research for the development of learning materials LKS interactions the ecosystem in class X SMA. Keywords: Community structure, Insect pollinators, Student Worksheet